Pengaruh Disiplin dan Lingkungan terhadap Motivasi Kerja dan Dampaknya pada Kinerja Pegawai di Dinas Tenaga Kerja dan Transmigrasi Provinsi Sumatera Selatan - Munawaroh, Istiqomah (Jurnal Ilmu Manajemen, 2018)
This research aims: (1) to find influence of work discipline and work environment simultaneously and partially to employees work motivation at Labor and Transmigration Department of South Sumatera Province, (2) to find influence of work discipline, work environment, and work motivation simultaneously and partially to employees performance at Labor and Transmigration Department of South Sumatera Province, and (3) to find influence of work discipline and work environment to employees performance through work motivation at Labor and Transmigration Department of South Sumatera Province.Design used in this research is regressional. Variables used are four variables, those are independent variables which Work Discipline (X1) and Work Environment (X2), intervening variable is Work Motivation (Y), and also dependent variable is Employees Performance (Z). Population in this research as much 257 persons. Sample used as much 72 persons. The analytical tool used is multiple linear regression.According to the research result, find: (1) There is a positive and significant effect work discipline and work environment simultaneously and partially to employees work motivation at Labor and Transmigration Department of South Sumatera Province, (2) There is a positive and significant effect work discipline, work environment, and work motivation simultaneously and partially to employees performance at Labor and Transmigration Department of South Sumatera Province, and (3) There is no significant effect work discipline and work environment to employees performance through work motivation at Labor and Transmigration Department of South Sumatera Province.